Non Sola Scriptura Essays on the Qur'an and Islam in Honour of William A. Graham (Taylor & Francis, 2022)
William A. Graham is an influential and pioneering scholar of Islamic Studies at Harvard University. This volume brings together 17 contributions to the study of the Qur'an and Islam, all influenced by his work Contributions to this collection, by his colleagues and students, treat many different aspects of Islamic scripture, from textual interpretation and hermeneutics to recitation and parallels with the Bible. Other chapters tackle in diverse ways the question of what it means to be ""Islamic"" and how such an identity may be constituted and maintained in history, thought, and learning. A final section reflects on the career of William Graham and the relation of scholarship to the undervalued tasks of academic administration, especially where the study of religion is concerned. This book will be of interest to readers of Islamic Studies, Qur'anic Studies, Islamic history, Religious Studies, scripture, exegesis, and history of the book. Given Graham's role at the Harvard Divinity School, and the discussions of how he has shaped the study of religion, the volume should be of interest to readership across the study of religion as a whole.
English
Keywords: History of religion; Islam; The Koran; islamic;koran;muhammad;religion;scripture;sunni